Observation of dust particles ejected from the tungsten surface by transient heat flux with small-angle scattering of cw laser light. (August 2017) - Vyacheslavov, L.N.; Arakcheev, A.S.; Burdakov, A.V.; Kandaurov, I.V.; Kasatov, A.A.; Kurkuchekov, V.V.; Mekler, K.I.; Popov, V.A.; Shoshin, A.A.; Skovorodin, D.I.; Trunev, Yu.A.; Vasilyev, A.A.
Highlights: ITER‐scale transients are simulated using a powerful sub‐millisecond electron beam. Small‐angle laser scattering technique is developed for in‐situ particles observation. Dynamics of particle generation at tungsten surface is investigated. Threshold near 180 MJ m ‐2 s ‐0.5 for intense ejection of particles is found. Temporal variation in size of particles, crossing the laser beam is estimated. Abstract: A new test facility for experimental simulation of transient heat load expected in the ITER divertor during unmitigated events is developed. Application of a long-pulse (0.1–0.3 ms) wide-aperture (up to 2 cm 2 ) electron beam as a heating device provides powerful energy loads at a tungsten target with FHF > 250 MJ m −2 s −0.5 . Dynamics of tungsten particles in the ablation plume is investigated with a novel for PSI experiments small-angle laser light scattering technique. The threshold of intense droplet generation and dynamics of particles sizes are estimated.